Lung Cancer in a Patient With Pulmonary Artery Sling: A Case Report - Mi, Jiahui; Wang, Xun; Li, Xiao; Liu, Yanguo; Jiang, Guanchao; Yang, Feng (Frontiers in Surgery, 2022)
Introduction Pulmonary artery sling (PAS) is a rare congenital vascular anomaly that results when the left pulmonary artery arises from the right pulmonary artery. There is little relevant literature on lobectomy for the treatment of lung cancer in patients with PAS, and the prognosis is unknown. Case Description A 54-year-old asymptomatic man was found to have a nodule on the left lower lobe of the lung, which measured 2.5 cm. The patient also had PAS. Three-dimensional computed tomography angiography confirmed that the left pulmonary artery arose from the right pulmonary artery and passed between the main trachea and the esophagus toward the left thorax. No obvious contraindication was found in the preoperative examination, and the patient successfully underwent lobectomy of the left lower lobe by video-assisted thoracoscopic surgery. Histological examination of the lesion revealed invasive adenocarcinoma. The postoperative course was uneventful, and no complications occurred in the subsequent 3 years of follow-up. Conclusions Lobectomy in a lung cancer patient with PAS did not increase perioperative risk and had no significant effect on prognosis.